Long-Lasting Effects of Incubation Temperature During Fetal Development on Subcutaneous Adipose Tissue of Broilers - Almeida, Ayla R. [UNESP]; Morita, Viviane S. [UNESP]; Matos Junior, João B.; Sgavioli, Sarah; Vicentini, Tamiris I. [UNESP]; Boleli, Isabel C. [UNESP] (Frontiers, 2022)
Increasing evidence indicates that fetal programming may cause permanent effects on offspring adipose tissue and body composition. Previous study showed reduction in newly-hatched broiler chick adiposity by manipulating incubation temperature during fetal development. The present study examined whether incubation temperature during fetal development has long-term effects on post-hatching fat deposition in broilers. Broiler breeder eggs (Cobb-500®) were incubated under constant low (36°C, LT), control (37.5°C, CT) or high (39°C, HT) temperature from day 13 onward, giving to eggshell temperature of 37.3 ± 0.08°C, 37.8 ± 0.2°C, and 38.8 ± 0.3°C, respectively. Male chicks were reared under recommended temperatures until 42 days old. LT 21 days old broilers exhibited higher blood cholesterol than CT broilers, and higher triglycerids, VLDL, and LDL, and lower HDL than CT and HT broilers. LT broilers presented higher liver cholesterol than CT broilers and lower ether extract percentage than CT broilers. Adipocyte count was lower in the abdomen than in the thigh. Until day 21 of age, feed intake was higher in LT than in HT broilers. At day 42 of age, blood cholesterol and LDL were higher in HT broilers than in CT and LT broilers. Liver cholesterol was higher in LT than in HT broilers. LT treatment reduced neck and increased thigh adipocyte size compared to CT treatment, while the HT treatment reduced abdomen and neck adipocyte size compared to other two treatments and in the thigh compared to LT treatment. In CT broilers, thigh adipocytes were smaller than abdomen and neck adipocytes. HT treatment increased adipocyte number per area in the neck compared to LT and CT treatment, and LT and HT treatments reduced adipocyte count in the thigh compared to CT treatment. CT broilers presented higher adipocyte count in the thigh than the abdomen and neck, while HT broilers presented higher adipocyte count in the neck than the abdomen and thigh. Cell proliferation was lower in the abdomen than in the thigh. The results show incubation temperature manipulation during fetal development has long-term and distinct effects on regional adiposity, and can be used to modulate broiler fat deposition.
Keywords: adipose tissue cellularity; body composition; fat deposition; fetal programming; incubation temperature; lipid prolife